2015
DOI: 10.7554/elife.06487
|View full text |Cite
|
Sign up to set email alerts
|

Mass enhances speed but diminishes turn capacity in terrestrial pursuit predators

Abstract: The dynamics of predator-prey pursuit appears complex, making the development of a framework explaining predator and prey strategies problematic. We develop a model for terrestrial, cursorial predators to examine how animal mass modulates predator and prey trajectories and affects best strategies for both parties. We incorporated the maximum speed-mass relationship with an explanation of why larger animals should have greater turn radii; the forces needed to turn scale linearly with mass whereas the maximum fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 69 publications
0
52
0
Order By: Relevance
“…The bio-logging-derived measure has value for multiple behavioural contexts. Examples include studies on navigation, where m-print metrics could highlight the circling movement sometimes seen in animals seeking to orientate themselves [43], or research into the acquisition of food or avoidance of predation where associated turns could be quantified [44]. Stemming from this and, given that there is a cost to turning that depends on the extent of the turn angle and the angular velocity [16, 45] we expect m-print angular velocity metrics to relate to movement energetics in the same way as have acceleration-derived metrics, such as VeDBA and ODBA [9, 46].…”
Section: Resultsmentioning
confidence: 99%
“…The bio-logging-derived measure has value for multiple behavioural contexts. Examples include studies on navigation, where m-print metrics could highlight the circling movement sometimes seen in animals seeking to orientate themselves [43], or research into the acquisition of food or avoidance of predation where associated turns could be quantified [44]. Stemming from this and, given that there is a cost to turning that depends on the extent of the turn angle and the angular velocity [16, 45] we expect m-print angular velocity metrics to relate to movement energetics in the same way as have acceleration-derived metrics, such as VeDBA and ODBA [9, 46].…”
Section: Resultsmentioning
confidence: 99%
“…We think that this mainly results from our use of generic, simplified allometric equations to describe important parameters in the model, such as prey population densities, maximum accelerations and detection distances. Recent advances in the field of allometry have shown that the effect of body size can be more complicated than previously acknowledged (Hirt, Jetz, Rall, & Brose, ; Pawar et al, ; Wilson et al, ), although it is still predictable (Kiørboe & Hirst, ). Our model's predictability would certainly benefit from an increase in the realism of the allometric equations it uses.…”
Section: Discussionmentioning
confidence: 99%
“…We think that this mainly results from our use of generic, simplified allometric equations to describe important parameters in the model, such as prey population densities, maximum accelerations, and detection distances. Recent advances in the field of allometry have shown that the effect of body size can be more complicated than previously acknowledged (Pawar, Dell, & Savage, 2012; Wilson et al, 2015; Hirt, Jetz, Rall, & Brose, 2017), although it is still predictable (Kiørboe & Hirst, 2014). Our model’s predictability would certainly benefit from an increase in the realism of the allometric equations it uses.…”
Section: Discussionmentioning
confidence: 99%